Meneroka kesetaraan dan keadilan gender dalam gereja dan masyarakat Toraja - Tangirerung, Johana Ruadjanna; Wangania, Judith D. L.; Tapparan, Meike Roselyna (KURIOS, 2024)
Toraja society, which has a bilateral kinship system, accommodates matriarchal and patriarchal systems. This system has elements of equality. However, church and community life phenomena are still less visible, especially regarding leadership. This paper will further explore the existence of women in broader leadership through the historical experience of leadership in the Toraja Church. The method used is qualitative descriptive by presenting various realities of injustice from multiple surveys in general and the history of the leadership of the Toraja Church itself in accepting women as church officials. The discussion results are various causes of injustice, namely the influence of theological understanding from Zending, who came to Toraja, and the influence of patriarchal ideology. The conclusion is that it is necessary to continuously carry out gender literacy to the church and community regarding equality.   Abstrak Masyarkat Toraja yang sistem kekerabatannya bilateral, mengakomodasi baik sistem matriarkar maupun patriarkar. Sistem ini sejatinya memiliki unsur kesetaraan. Namun melihat fenomena dalam kehidupan gereja dan masyarakat, masih kurang terlihat, khususnya terkait kepemimpinan. Tulisan ini akan meneroka lebih jauh keberadaan perempuan dalam kepemimpinan yang lebih luas melalui pengalaman sejarah kepemimpinan dalam Gereja Toraja. Metode yang digunakan adalah kualitatif deskriptif dengan mengemukakan berbagai realitas ketidakadilan dari berbagai survei secara umum dan realitas dalam sejarah kepemimpinan Gereja Toraja sendiri dalam menerima perempuan menjadi pejabat gerejawi. Hasil pembahasan adalah ditemukan berbagai sebab ketidakadilan yaitu pengaruh pemahaman teologi dari Zending yang datang ke Toraja dan pengaruh ideologi patriarkalisme. Riset ini menyimpulkan, perlunya terus-menerus melakukan literasi gender kepada gereja dan masyarakat terkait kesetaraan.